Eysenck's model of personality and prayer: the utility of a multidimensional approach - Breslin, Michael J. (Mental health, religion & culture, 2014)
Previous research has confirmed that psychoticism is the dimension of personality that is fundamental to individual differences in prayer. However, overwhelmingly researchers have employed a single-item prayer measure. It may be that different types of prayer relate to personality differentially. The present aim was to examine the relationship between a multidimensional prayer measure and Eysenck's model of personality to ascertain if personality can be differentially predicted by different types of prayer and to investigate if a multidimensional measure of prayer has utility over a single-item measure. A sample of 282 Irish respondents completed the measure of prayer type and the abbreviated form of the Revised Eysenck Personality Questionnaire. Hierarchical multiple regression showed that ritual prayer was the only significant independent predictor of personality, predicting psychoticism only. Results suggested that a multidimensional measure of prayer has limited utility over a single-item measure.